Aspetti e frontiere del racconto biografico - Adamo, Pier Giovanni (Status Quaestionis, 2024)
The present essay attempts to demonstrate how and why 19th century forms and 20th century variants of biofiction mark an important paradigm shift in the recent history of the literary field. They prove that in the narrative genres of contemporary age life is not perceived as the object of an integral representation but is rather treated as the subject of a recognition, that of a reality as fragmentary as the manners of an art founded on the temporal imbalance between βίος and fiction. The essay aims to clarify aspects and frontiers of biofiction dating back to European modernity: the fictional matrix that is implied in the dynamic between narrativization and reconstruction; the illusory rigour of completeness; the constant fragmentariness; the alternation between topics of uniqueness and discourse of infamy; the atmospheric definition of the untimely – with the purpose of providing, through a combined exercise of theoretical morphology and diachronic genealogy, the fundamental coordinates for the metahistorical interpretation of modern biofiction.